Impact of Using Extension Suite Online System as Solution for Subsistence Farming in Rural Areas: The Role of Universities - Uleanya, Chinaza; Oki, Olukayode; Lukose, Jose Manappattukunnel (Technium Social Sciences Journal, 2021)
Agriculture plays an important role in economic development especially in rural areas because it provides source of employment and sustainable livelihood. Meanwhile. Information Communications Technologies (ICTs) have brought to the fore more efficient ways of information dissemination and there is a general realization that information technology should be integrated to be effectively used in agricultural development. This study explored the impact of using Extension Suite Online System for subsistence farming using Qunu Area in Eastern Cape province. Quantitative method was adopted for the study. Data was collected through the use of questionnaire from 25 conveniently selected farmers and were analysed using Statistical Package for the Social Sciences (SPSS). The finding of the study amongst others showed that the introduction of Extension Suite Online system to the Qunu rural farmers managed to close the information gap that was initially a challenge and it fascinated young people who perceived agriculture as a sector for older people. Also the change in employment dynamics in the farming industry of South Africa, with women taking higher positions as women are now actively involved in farming activities. However, it was pointed out following the responses of the respondents that most farmers in the rural area are computer illiterates and this affects their appreciation and use of ESO system. The study recommends amongst others that alliance between universities and rural farmers should be formed. Also, short term programmes which promote computer literacy and other useful skills should be made available for rural farmers by universities.